Transnational ties with the African extended family in mixed families in Italy - (:unkn) unknown (My University, 2020)
Maintaining links with the family of origin is a key issue for the transmission of the sense of belonging to children when only one of the parents is a migrant. The article focuses on the transnational intergenerational ties developed by mixed families in a postcolonial context. Based on a survey carried out in Italy between 2016 and 2017 among couples composed of an Italian parent and a sub-Saharan parent, the article addresses the practices of maintaining ties, from a distance and in the presence, as well as the constraints perceived by parents to keep them. The analysis of the results reveals the role of the migratory context, economic conditions, prejudices and gender in family dynamics.
Keywords: African Research